Strategi Implementasi Program Gerakan Literasi Sekolah Berdasarkan Evaluasi Komprehensif Di SMP Bina Insani Kota Bogor - Suwarni, Suwarni; Hendarman, Hendarman; Herfina, Herfina (JURNAL MANAJEMEN PENDIDIKAN, 2024)
STRATEGY FOR IMPLEMENTATION OF SCHOOL LITERACY MOVEMENT PROGRAM BASED ON A COMPREHENSIVE EVALUATION AT SMP BINA INSANI KOTA BOGOR This research aimed to analyze the implementation of the School Literacy Movement (SLM) program at SMP Bina Insani Kota Bogor using evaluative research methods with the CIPPO model which included the components of context, input, process, product and outcomes. The aspects evaluated were those that had gone well and those that were still not optimal as a basis for policy making in the following years. Data collection was carried out through techniques of interview, observation and documentation studies. The informants were determined using purposive sampling. The data analysis technique used the Miles and Huberman model, namely data reduction, data display and conclusions. The results of the research showed that of the 4 aspects in the context component evaluated, each received "Very Good" score category, of the 6 aspects in the input component evaluated, 2 aspects received "Good" score category and 4 aspects received "Very Good" score category, of the 5 aspects in the process component evaluated, 3 aspects received "Good" score category and 2 aspects received "Very Good" score category, 1 aspect evaluated in the product component received "Very Good" score category, and 2 aspects evaluated in the outcomes component, each received "Very Good" score category. Thus, the implementation of the School Literacy Movement (SLM) program at SMP Bina Insani Kota Bogor had generally been conducted very well with an achievement rate of 93.05% and could be continued with 2 aspects in the input component and 3 aspects in the process component were still allowing for improvement.